Balance of payments adjustment through public absorption an estimation of an ARDL model in a panel of MENA and eastern European countries - BENSBAHOU Aziz; TALBI Abdelghani (African Scientific Journal, 2022)
One of the most difficult problems in the field of public economic policies and their effects on the fundamental macroeconomic variables lies in their impact on the external sector variables; hence the need to control public expenditure in proportions that are deemed useful and that would be compatible with the objectives set in order to ensure the fundamental balances at both the internal and external levels. The purpose of this article, from this perspective, is to focus on the balance of payments adjustment through public absorption, for a sample of 11 countries from the MENA region and the European continent. By bursting public absorption in two fundamental components: public consumption and public investment, we highlight how action on these two main components could adjust the balance of payments balances for the selected countries. Adopting the lessons of the absorption approach, often referred to as fiscal or financial, as a comprehensive approach to balance of payments adjustment, we will estimate an ARDL panel model using advanced panel data modelling techniques. Our empirical results underline the existence of a short- and long-term adjustment relationship between public absorption and external balances, regardless of the method adopted to measure them: external balance of goods and services or current account balance. These empirical results corroborate the prediction of the Keynesian Absorption Hypothesis and reject the Ricardian Hypothesis that there is no link between internal and external balances. Therefore, we discuss the implications of our results to highlight the main measures that would be consistent with macroeconomic adjustment policies, especially for MENA countries where internal and external imbalances are more persistent compared to the European continent.